Leucine-included liquid diet as medical nutrition therapy improved handgrip strength and mid-upper circumference in clinically malnourished pulmonary tuberculosis patient with high neutrophil lymphocyte ratio: A case report from Universitas Indonesia hospital - Singal, Anna Maurina; Afifa, Nadhira Nuraini; Wardhani, Wahyu Ika; Baskoro, Hario (Indonesian Nutrition Association, 2025)
Background and objectives: Muscle weakness delays clinical improvement in pulmonary tuberculosis patients. Higher neutrophil lymphocyte ratio, low handgrip strength, mid-upper arm circumference indicates bad clinical outcome. Weight loss must be managed from the start of treatment. Good muscle condition has benefits to the recovery rate. Leucine provides benefits in increasing the synthesis of muscle mass so as the clinical conditions. Unfortunately, leucine has not been the routine part of medical nutrition therapy in tuberculosis patients. Methods: This is a case report of a female patient with body weight 42 kg and height 150 cm, admitted to Universitas Indonesia Hospital, with lung tuberculosis. Leucine given, started from 1.95 g/day to the maximum amount of 7,34 g/day through the hospital tailored-made liquid food. There was an improvement of clinical signs and symptoms during 14 days of hospitalization. Mid-upper arm circumferences at day 1, 8, and 15 were 21.1, 21.4, and 12.9 21.9 cm in a row. The right and left handgrip strength at day 1, 8, and 15 were 9.7 kg and 8.1 kg, 10.9 kg and 8.9 kg, 15.1 kg and 13.4 kg, respectively. While the neutrophil lymphocyte ratio at day 0, 6, and 9 were increasing, at 6.89, 6.89, and 13.8, in a row. Conclusions: Leucine 1.95–7.34 g/day, in tailored-made liquid food, as part of tuberculosis management therapy, though the NLR 13.8, can improve the mid-upper arm circumference, handgrip strength, clinical signs and symptoms in 14 days of hospitalization.